Modification and Performance Test of A Tube Type Pressure Stove using Jatropha curcas Oil Fuel - Hastono, Abi D.; soebandi, Soebandi; Fatah, Gatot Suharto Abdul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
Energy crisis is a problem that still has not been fully resolved. Kerosene as one of the main source of energy for daily cooking is relatively expensive. It can cost up to Rp. 8000,-/L. Although energy conversion from kerosene to LPG has been carried out by the government of Indonesia, but some users still prefer kerosene for security reasons. Until now, pressure stove or kerosene-fueled stoves commonly called tube type are still used by users to fry fried foods. By modifying mainly on the part of the wind shield tube it is spected that presure stove tube type can be used bio oil. Some bio-oil which come from jatropha curcas, cottonseed oil and kapok oil have potential to be used as bio fuel. The aim of the research and modification was to get pressure stoves prototype by using bio-oil by modification of pressure stoves as a substition of kerosene pressure stoves. The result of modification and engineering of pressure stoves, could be got some prototypes pressure stoves that was pressure stove tube type. The result performance test is done using jatropha oil as follows : fuel consumption 1250 mL/ hour; pre-heating 17 minutes; boiling time of 2 litre of water 5 minutes; the noise levels was 88.2 dB and the flame colour was reddish blue.Keywords: modification, pressure stove, Jatropha curcas, fuel oil.